Pengaruh Putusan MK NOMOR 1/PUU-XXI/2023 Terhadap Sikap Politik Mahasiswa Fakultas Hukum Universitas Jambi - Raihan Edwar Saputra; Tichin Rosevel Pandiangan; Aulia Sindi Pifua; Agiel Sabigul Okhir (Universitas Sains dan Teknologi Komputer, 2024)
This research discusses the role and authority of the Constitutional Court as a high state institution that exercises judicial power in the constitutional system of Indonesia. This research also examines the impact of the Constitutional Court’s decisions on the administration of the state, especially related to the minimum age of presidential and vice-presidential candidates that became controversial ahead of the 2024 election. This research aims to analyze the progressive legal interpretation used by the Constitutional Court in reviewing laws that are contrary to the 1945 Constitution, and to find out its influence on the political attitude of law students at Jambi University.